Hidrelétricas na Amazônia são fontes de energia limpas? Emissões diretas e indiretas pela mudança de cobertura do solo e emissões de créditos de carbono pela Usina Hidrelétrica Teles Pires. - Clara Nina Rodrigues Nunes (2018)
Climate change caused by greenhouse gas (GHG) emissions has become a major environmental problem in recent decades. In order to articulate a joint solution to this problem, the United Nations (UN) created the United Nations Framework Convention on Climate Change (UNFCCC) in 1992. The UNFCCC signed the Kyoto Protocol in 1998, which sets targets for the reduction GHG emissions to developed countries (Annex I) and encourages mitigation actions in developing countries (not Annex I) through the Clean Development Mechanism (CDM). The CDM permits the issuance of Certified Emissions Reduction (CER) that can be acquired by the Annex I countries to fulfill part of their project financing goals in non-Annex I countries that have financial additionality and environmental additionality. The latter is defined by methodologies developed in line with the publications of the Intergovernmental Panel on Climate Change (IPCC) and approved by the CDM Executive Committee within the UNFCCC. In Brazil there are 68 Project Design Documents (PDD) in energy generation by water source submitted to the CDM. Among them is the Teles Pires hydroelectric plant (HPP) project that received CERs of 24,994 million tCO2e. Although considered a viable option for energy production, the HPPs received questions about the calculation of greenhouse gas emissions from reservoirs. In the case of the HPP this problem is even greater because the implementation of these large enterprises is often accompanied by deforestation of large areas in the affected regions. This dissertation contributes to this debate when considering the indirect emissions generated by the deforestation related to the population increase and the construction of roads linked to these enterprises. The proposal of this study considers the influence of the project on the deforestation in a radius of up to 150 kilometers of the dam on the Teles Pires river, and compares the already deforested and projected deforestation from 2011 to 2025 (final year of the PDD) with that of the HPP, and a factual scenario that simulates the absence of the hydroelectric plant. The result of the simulation indicates that the implementation of the Teles Pires HPP will cause in the 15-year period the additional loss of 6021.84 km² of native forests in the Amazon, generating an atmospheric impact of 61.4 million tons of CO2 equivalent (MtCO2e). When considering the indirect emissions caused by the HPP, the submitted CDM project would pass from issuer of CERs to climatic creditor, necessitating the purchase of 36,446 MtCO2e to have emissions comparable to that of a thermoelectric of the same size. Such information demonstrates the relevance of the studies in this branch that collaborates to the development of methodologies that meet the environmental impacts generated by the HPP and collaborate to the development of effective public policies on the environmental problems.